2008
DOI: 10.1089/fpd.2008.0048
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Incidence and Molecular Characterization ofSalmonellafrom Dairy Cows, Calves, and Farm Environment

Abstract: The occurrence patterns and molecular characteristics of Salmonella are important for surveillance and control of the pathogens. Objectives of this study were to determine month-to-month variation and seasonal effects on the occurrence of Salmonella in dairy animals and environments and to characterize selected Salmonella isolates. A total of 7680 animal and environmental samples, collected monthly from a dairy farm, were analyzed for the presence of Salmonella during a 12-month study. Major sources of Salmone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 21 publications
(23 reference statements)
2
4
0
Order By: Relevance
“…In fact, it is known that cattle kept in a hospital settings are at risk of salmonellosis due to the presence of several predisposing factors, such as affected gut microbiota by antimicrobial and proton bomb inhibitors administration, concurrent diseases and status of immunossuppression (EWART et al, 2001;CUMMINGS et al, 2009). Additionally to these risk factors, previous reports have also shown a higher fecal shedding of Salmonella spp among hospitalized and dairy cattle in the summer and fall (PANGLOLI et al, 2008;CUMMINGS et al, 2009). Interestingly, the outbreak of Salmonella Typhimurium described in the present study occurred during the summer months in Brazil, corroborating with previous researches.…”
Section: Resultssupporting
confidence: 92%
“…In fact, it is known that cattle kept in a hospital settings are at risk of salmonellosis due to the presence of several predisposing factors, such as affected gut microbiota by antimicrobial and proton bomb inhibitors administration, concurrent diseases and status of immunossuppression (EWART et al, 2001;CUMMINGS et al, 2009). Additionally to these risk factors, previous reports have also shown a higher fecal shedding of Salmonella spp among hospitalized and dairy cattle in the summer and fall (PANGLOLI et al, 2008;CUMMINGS et al, 2009). Interestingly, the outbreak of Salmonella Typhimurium described in the present study occurred during the summer months in Brazil, corroborating with previous researches.…”
Section: Resultssupporting
confidence: 92%
“…samples being positive in district D. G. Khan. The results of present study are in agreement with the finding of Pangloli et al [22] who isolated 40-92% Salmonella spp. from animal and environment samples.…”
Section: Discussionsupporting
confidence: 94%
“…In soils and manures, warmer temperatures may facilitate survival. For instance, a survey of east Tennessee dairy farms found that Salmonella was more readily isolated from animal and environmental samples as ambient temperatures increased [ 31 ]. The current study was originally designed to examine seasonality, but farm participation and sample availability impacted when litter could be collected.…”
Section: Discussionmentioning
confidence: 99%